Protocolo in silico para el diseño de potenciales inhibidores de la proteasa principal 3clpro del nuevo coronavirus sars-cov-2 (2020)
To date, around 62 million positive cases of COVID-19 have been reported globally. The International Committee on Taxonomy of Viruses (ICTV) named this coronavirus as SARS-CoV-2. There are several crucial proteins involved in the SARS-CoV-2 replication cycle, one of those is the Mpro main protease protein, also known as the 3CLpro protein. Due to the pandemic, the information about the main protease is increasing day by day. However, there are knowledge gaps involved during important processes such as dimerization. On the other hand, to date, no powerful tools have been developed that allow a quick search of 3CLpro inhibitors, such as pharmacophore models. In other studies, protease inhibitor pharmacophoric models have been designed, but none have been used in virtual screening processes due to the lack of model validation. To fill these knowledge gaps, in this study, a protocol composed of molecular dynamics (MD) simulations, molecular docking, free energy calculations and pharmacophore modeling was executed. In this protocol, a molecular dynamics simulation of Mpro protein in apo form and 55 molecular dynamics simulations of Mpro protein-ligand complexes with several inhibitors were performed. The molecular dynamics simulations were employed to design two protein-ligand based pharmacophore models. One of these two models includes the electrophilic group feature, a novel feature in pharmacophore modeling. It?s expected to use the pharmacophore models to design SARS-CoV-2 Mpro protease inhibitors that can function as a treatment for COVID-19.